Proenkephalin expression and enkephalin release are widely observed in non-neuronal tissues - Denning, Gerene M.; Ackermann, Laynez W.; Barna, Thomas J.; Armstrong, John G.; Stoll, Lynn L.; Weintraub, Neal L.; Dickson, Eric W. (Peptides (New York, N.Y. : 1980), 2008)
Enkephalins are opioid peptides that are found at high levels in the brain and endocrine tissues. Studies have shown that enkephalins play an important role in behavior, pain, cardiac function, cellular growth, immunity, and ischemic tolerance. Our global hypothesis is that enkephalins are released from non-neuronal tissues in response to brief ischemia or exercise, and that this release contributes to cardioprotection. To identify tissues that could serve as potential sources of enkephalins, we used real-time PCR, Western blot analysis, ELISA, immunofluorescence microscopy, and ex vivo models of enkephalin release. We found widespread expression of preproenkephalin (pPENK) mRNA and production of the enkephalin precursor protein proenkephalin (PENK) in rat and mouse tissues, as well as in tissues and cells from humans and pigs. Immunofluorescence microscopy with anti-enkephalin antisera demonstrated immunoreactivity in rat tissues, including heart and skeletal muscle myocytes, intestinal and kidney epithelium, and intestinal smooth muscle cells. Finally, isolated tissue studies showed that heart, skeletal muscle, and intestine released enkephalins ex vivo. Together our studies indicate that multiple non-neuronal tissues produce PENK and release enkephalins. These data support the hypothesis that non-neuronal tissues could play a role in both local and systemic enkephalin-mediated effects.